In vivo profiling of the PE/PPE proteins of Mycobacterium tuberculosis reveals diverse contributions to virulence - Koleske, Benjamin; Shen, Jessica; Gupta, Manish; Bishai, William R. (Frontiers in Microbiology, 2025)
Mycobacterium tuberculosis (M.tb) uses a plethora of cell surface and secreted virulence factors to survive within the host. Among these are the PE/PPE proteins, a pair of secretory families that have expanded to 168 members in M.tb. Most of these proteins are poorly characterized due in part to their repetitive sequences and high similarity to one another. While PE/PPE genes are generally non-essential in vitro, many are highly expressed during animal infection. Thus, we conducted an in vivo pooled screen of 87 transposon mutants in M.tb PE/PPE genes and used Tn-seq to identify mutants with fitness defects in the mouse lung environment. We found consistent, time-dependent changes in mutant abundance across our animal replicates and identified decreases in several key mutant strains known to promote bacterial growth or virulence. In all, 27 of the 87 mutants showed significant reductions in percent population prevalence in the lung over 3 weeks. We then selected a transposon mutant in the PPE71 gene and validated that this strain was attenuated in a single-strain infection. Our findings suggest that a high proportion of PE/PPE genes (31%) are required for virulence in the mouse model. These observations suggest that individual PE/PPE genes have differing contributions to virulence and may help prioritize future studies of these families. Strikingly, these properties were seen only in an in vivo model, which may imply a role for PE/PPE proteins in M.tb host-pathogen interactions.